Increased risk of rhinitis symptoms in subjects with gastroesophageal reflux. (June 2014) - Hellgren, Johan; Olin, Anna-Carin; Torén, Kjell
Abstract Conclusion: This study shows that gastroesophageal reflux and tobacco smoke are associated with adult-onset non-infectious rhinitis (NIR). The results support an association between gastroesophageal reflux and upper airway inflammation. Objectives: To examine the incidence of adult-onset NIR in relation to several risk factors. Methods: This is a follow-up study of 3307 randomly selected men and women aged 25–75 years from a general population-based sample. At baseline, the subjects were investigated with questionnaires, a pulmonary function test, blood samples, and FENO. At follow-up 4 years later, all the subjects were mailed a respiratory questionnaire. The incidence of NIR and associated risk factors, such as smoking, atopy, asthma, cough, obesity, and gastroesophageal reflux, was assessed. Results: The response rate at follow-up was 92%. The incidence of new-onset NIR was 14.9/1000 person-years (n = 247). In a regression model including age, gender, obesity, asthma, cough, and atopy, both current smoking (OR 1.7, 95% CI 1.2–2.5, p = 0.002) and gastroesophageal reflux (OR 2.5, 95% CI 1.4–3.1, p < 0.001) were significantly associated with adult-onset NIR.